A study on the judicial involvement in a plea bargaining process in Malaysia / Mohd Akmal Mohd Ramlel…[et al.] - Mohd Ramlel, Mohd Akmal; Rasmi, Muhammad Abdullah; Ab Rahim, Nur Ayuni; Ruslan, Shairil Farhana (2010)
This project paper will be touching on the issue of judicial involvement in a pleabargain agreement. In this document, we have included the history, the amendment made to the Criminal Procedure Code and an analysis of the impact of the judicial involvement in the course of a plea-bargain agreement. A sort of introduction to what is plea-bargaining is provided before an in-depth analysis into the impact of judicial involvement in such transactions is laid-down. The analysis is basically derived on scrutinizing the bill amendment of the Criminal Procedure Code and also through conduct of interviews of members of the commission that had drafted the said bill. Based on these interviews, we have gained an insight as to the hopes of the legal practitioners in our country through the implementation of this legal option. As Malaysia has yet to officially practice pleabargaining, an analysis of the various degrees of judicial involvement in a pleabargaining process all around the world is also provided in order to clarify the consequence of a minimal or active participation by the courts. Through this comparison, we had managed to observe and analyze whether or not the present provision for plea-bargaining in Malaysia is suitable and adequate to cater to the problem of backlog of cases in our courts but also ensure the administration of justice at the same time.